2009
DOI: 10.1128/jcm.02222-08
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Identification and Susceptibility ofTrichosporonSpecies Isolated from Clinical Specimens in Qatar: Isolation ofTrichosporon dohaenseTaj-Aldeen, Meis & Boekhout sp. nov

Abstract: Trichosporon species have been reported as emerging pathogens and usually occur in severely immunocompromised patients. In the present work, 27 clinical isolates of Trichosporon species were recovered from 27 patients. The patients were not immunocompromised, except for one with acute myeloid leukemia. Sequence analysis revealed the isolation of Trichosporon dohaense Taj

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
76
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 79 publications
(77 reference statements)
2
76
1
Order By: Relevance
“…The automated commercially available Vitek 2 system identified the majority of isolates only to the genus level. Additionally, 27 of 51 isolates of basidiomycetous arthroconidial yeasts were identified previously by molecular methods (15). The remaining isolates were analyzed by ITS and LSU bar-coding during this study.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The automated commercially available Vitek 2 system identified the majority of isolates only to the genus level. Additionally, 27 of 51 isolates of basidiomycetous arthroconidial yeasts were identified previously by molecular methods (15). The remaining isolates were analyzed by ITS and LSU bar-coding during this study.…”
Section: Methodsmentioning
confidence: 99%
“…Use of the automated Vitek 1 and 2 systems (bioMérieux) has increased lately, but the Vitek 2 database includes only three Trichosporon and three Geotrichum species (17)(18)(19). Consequently, identifications usually are unreliable (15,17,18,20).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Trichosporon faecale is an environmental fungus found mainly in soil [4]. Although T. faecale is generally considered to be non-pathogenic, it has been isolated from clinical specimens in Argentina [11], Brazil [12,13], Egypt [14], Qatar [14], Turkey [15], Spain [11], and Taiwan [16]. In the present study, we found that T. faecale was part of the fungal skin microbiome in Japanese subjects and that the genotype of the microorganism was of a single type.…”
Section: Introductionmentioning
confidence: 99%